Biochemical characterization of a novel acidophilic β-xylanase from Trichoderma asperellum ND-1 and its synergistic hydrolysis of beechwood xylan - Zheng, Fengzhen; Basit, Abdul; Zhuang, Huan; Chen, Jun; Zhang, Jianfen; Chen, Weiqing (Frontiers in Microbiology, 2022)
Acidophilic β-xylanases have attracted considerable attention due to their excellent activity under extreme acidic environments and potential industrial utilizations. In this study, a novel β-xylanase gene (Xyl11) of glycoside hydrolase family 11, was cloned from Trichoderma asperellum ND-1 and efficiently expressed in Pichia pastoris (a 2.0-fold increase). Xyl11 displayed a maximum activity of 121.99 U/mL at pH 3.0 and 50°C, and exhibited strict substrate specificity towards beechwood xylan (Km = 9.06 mg/mL, Vmax = 608.65 μmol/min/mg). The Xyl11 retained over 80% activity at pH 2.0-5.0 after pretreatment at 4°C for 1 h. Analysis of the hydrolytic pattern revealed that Xyl11 could rapidly convert xylan to xylobiose via hydrolysis activity as well as transglycosylation. Moreover, the results of site-directed mutagenesis suggested that the Xyl11 residues, Glu127, Glu164, and Glu216, are essential catalytic sites, with Asp138 having an auxiliary function. Additionally, a high degree of synergy (15.02) was observed when Xyl11 was used in association with commercial β-xylosidase. This study provided a novel acidophilic β-xylanase that exhibits excellent characteristics and can, therefore, be considered a suitable candidate for extensive applications, especially in food and animal feed industries.